2019
DOI: 10.3390/rs11242991
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Surge-Type Glaciers in the Yangtze River Headwater Using Multi-Source Remote Sensing Data

Abstract: A surge-type glacier is a special and dangerous type of glacier, which can advance quickly in a short-time with cycles. Glaciers in the Yangtze River headwater are generally acknowledged to be in a stable state. However, not all of those glaciers are stable. In this paper, five glaciers from the Yangtze River headwater glacier were selected as the experimental subjects, and multi-source remote sensing images were used to study and analyze the surge behavior over the past 30 years. Based on the Landsat series d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The surging lasted for ~3 years, resulting in the terminus advancing by 500 ± 11.2 m, pushing the medial moraine southeastwards 302 ± 11.3 m. The maximum velocity occurred between 28 August and 2 December 2014, and was 1100 m a −1 (3 m d −1 ). It has comparable maximum velocity and similar surging duration with its two adjacent surge-type glaciers (G091091E33424N and G091071E33463N) (Yan and others, 2019), which have a similar area as Gangjiaquba (27.03 ± 0.83 and 34.92 ± 1.08 km 2 ) (Xu and others, 2018). The maximum velocity observed in our study is about seven times as that observed by King and others (2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surging lasted for ~3 years, resulting in the terminus advancing by 500 ± 11.2 m, pushing the medial moraine southeastwards 302 ± 11.3 m. The maximum velocity occurred between 28 August and 2 December 2014, and was 1100 m a −1 (3 m d −1 ). It has comparable maximum velocity and similar surging duration with its two adjacent surge-type glaciers (G091091E33424N and G091071E33463N) (Yan and others, 2019), which have a similar area as Gangjiaquba (27.03 ± 0.83 and 34.92 ± 1.08 km 2 ) (Xu and others, 2018). The maximum velocity observed in our study is about seven times as that observed by King and others (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Geladandong Peak in the Central Tibetan Plateau is the highest mountain in the source region of the Yangtze River (Figs 1a, b). There were 19 surge-type glaciers identified based on elevation and velocity changes analysis (Yan and others, 2019; Gao and others, 2021; King and others, 2021).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Combining with the first and second Chinese Glacier Inventory datasets, we explored the length change of these nine glaciers between 1970-2018. Some of the nine glaciers were classified as surge-glaciers in some studies (Yan et al, 2019;Guo et al, 2020;King et al, 2021), and their criteria include: (1) rapid advance of glacier terminus; (2) ve There are two well-known theories on the trigger mechanism of glacier surge: thermal control (Kamb, 1987) and hydrological control (Murray, 2003). However, these two mechanisms are summarized from field investigation in Alaska (Kamb et al, 1985) and Svalbard (Murray, 2003), the mechanism for surge-glaciers in the Tibetan Plateau are ambiguous (Paul, 2020).…”
Section: The Advance/surge Glaciersmentioning
confidence: 99%
“…Table 6. Averaged geometric information (area, slope, maximum length, and maximum/minimum/ medium elevation) of glaciers in nine surging regions and the summary of the surge duration, period, maximum velocity (m a −1 ), and terminus advance (km) for STGs in different regions of HMA [3,[8][9][10][11]15,25,[32][33][34]. We use the symbol-when no values are specified.…”
Section: Surge Characteristicsmentioning
confidence: 99%
“…Lovell and others [11] found that while at Sabche Glacier in the central Himalayas, surges are likely to be facilitated by subglacial processes, the subglacial topography of the glacier appears to modulate both the timing and duration of each surge [11]. STGs have also been well-documented in the Geladandong Mountain [31,32], Xinqingfeng, Malan Ice Caps [33], and Zangser Kangri Ice Field areas [34]. Recently, terminus advance has been reported for some glaciers in the TJP region, the QLMs; however, a newer list of confirmed surges for the entire area has not been undertaken [35].…”
Section: Introductionmentioning
confidence: 98%